Sistem Pendeteksi Alkohol Berbasis Sensor MQ-3 dan Internet of Things - Alviansyah Oktario Pratama; Ade Rohdiana; Rahma Rosaliana Saraswati (IAIN Salatiga, 2020)
Today more and more food and beverages are mixed with some types of alcohol in disguise. Fatwa MUI No.4 Year 2003 states that